Insecticidal efficacy of native raw and commercial diatomaceous earths against Tribolium confusum DuVal (Coleoptera: Tenebrionidae) under different environmental conditions - Ogreten, Ayhan; Eren, Sedat; Kaya, Cahit; Mutlu, Cetin; Ayaz, Tarkan; Gaafar, Abdel-Rhman Z.; ul Malook, Saif (Elsevier, 2023)
Background: Stored wheat grains are infested by several insect pests which lead to notable financial losses, compromised food security, and higher wastage. The confused flour beetle [Tribolium confusum DuVal (Coleoptera: Tenebrionidae)] is a widespread pest infesting stored flour and grains. Pest management in stored wheat requires ecofriendly option with lower toxicity to stored grains. Diatomaceous earths (DEs) are considered environment-friendly, green insecticides and often used to manage stored product pests.Methods: This study determined the impacts of different temperatures, relative humidity levels, and doses on the efficacy of three DEs [i.e., two raw native (Ankara, and Aydin), and one commercial (Silico-Sec)]. Two temperatures (25 degrees C and 30 degrees C), two relative humidity levels (40% and 60%) and five doses (0, 250, 500, 750 and 1000 ppm) of the tested DEs were included in the study. Different DE doses were mixed with 500 g of wheat grains in plastic containers and 30 adults of T. confusum were released. The containers were kept under different temperature and relative humidity levels according to the treatments and mortality data was recorded at 7, 14 and 21 days after treatments (DAT).Results: The mortality linearly increased with increasing time intervals and DEs doses. The highest and the lowest mortality was noted at 21 and 7 DAT, respectively. All DEs caused higher mortality under 30 degrees C temperature, 40% relative humidity and 1000 ppm dose. The native DE Aydin and commercial DE Silico-Sec caused comparable mortalities.Conclusion: Overall, the highest mortality was recorded with 1000 ppm dose of all DEs under 30 degrees C temperature and 40% relative humidity. Therefore, the DEs must be applied at these environmental conditions for getting higher efficacy. Furthermore, the native DE Aydin could be utilized to manage T. confusum in the granaries. The farmer granaries in the region have similar temperature and relative humidity conditions; therefore, the DEs can be successfully used to lower the damages caused by T. confusum at farmers' level.(c) 2023 The Author(s). Published by Elsevier B.V. on behalf of King Saud University. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Native diatomaceous earths; Environmental factors; Temperature; Humidity; Mortality